SHIPPERS’ SWITCHING BEHAVIOR TOWARD GREEN VEHICLES IN LAST-MILE DELIVERY: EVIDENCE FROM A DEVELOPING COUNTRY - Xuan Cu Le; Tran Hung Nguyen (Journal of Applied Structural Equation Modeling, 2025)
The present study aims to determine how value perceptions and green trust influence shippers’ intention to switch toward green vehicles for last-mile delivery. Additionally, it explores the impact of green knowledge on value perceptions and the subsequent effect of these perceptions on green trust in these vehicles. A convenience sampling approach was used to recruit 352 shippers utilizing conventional vehicles for last-mile delivery in Vietnam. The collected data were then examined using covariance-based structural equation modeling in AMOS version 21.0. The findings reveal that green knowledge fosters value perceptions, including functional, emotional, social, and epistemic values. These dimensions cultivate green trust and switching tendency. Notably, green trust plays a vital role in shippers’ decision to switch to green vehicles for lastmile delivery. This study extends the theory of consumption values by introducing green knowledge as a key driver of value perceptions and by positioning these perceptions as antecedents that facilitates green trust. The results are meaningful for manufacturers and logistics companies to understand shippers’ perspectives and switching decisions from the lens of green knowledge, value perceptions, and green trust.